(untitled) (Stavební obzor - Civil Engineering Journal, 2017)
Recirculation of airflows in a mine ventilation system can cause concentration of contaminated air which results in an unsafe working environment for people working in an underground mine. Due to the difficulty in finding the recirculation of airflows in complicated mine ventilation system, depth-first search method is proposed to find the recirculation of airflows in complicated mine ventilation systems. The searching procedure of a simply depth-first search method is introduced briefly. Then the depth-first search method is modified for searching recirculation of airflows in complicated mine ventilation systems. The proposed method is implemented through MATLAB in the form of storing ventilation information in a matrix. A few recirculation of airflows are found and are confirmed by the mine ventilation simulation result. It is concluded that the proposed method is a valuable tool in finding recirculation of airflows in a complicated mine ventilation system.